Evaluating the multifaceted impact of Cephalaria extract on dough quality: Antioxidant, antimicrobial, and cytotoxic properties - Bagdat, Elif Seyma; Bozkurt, Fatih; Ilikkan, Ozge Kahraman; Sagdic, Osman; Tornuk, Fatih (WILEY, 2024)
Cephalaria syriaca, known as cephalaria, is an annual, pilose plant with pink-purple flowers growing wild in wheat fields. Viscoelastic properties of gluten-free doughs can be improved by adding cephalaria. However, this addition results in some undesirable properties in bread such as bitter taste and dark internal colour. This study aimed to reduce these effects by obtaining cephalaria obtained from distilled water and ethanol extracts and to increase the potential use of extracts in bread production. Different proportions of water and ethanol extracts obtained from oil-free cephalaria were added to bread by creating a model with Mixture Design, and the optimum concentration was determined by farinograph trials. The antioxidative, antimicrobial, and cytotoxic effects of extract and the effect of cephalaria on yeast activity were examined. Cephalaria extracts had no measurable antimicrobial effect and no antifungal effect on Rhizopus stolonifer, while an antifungal effect was found against A. niger and P. expansum. The IC50 value was found to be 4.15 mg mL(-1 )for ethanol extract while the water extract had no effect on cells. The addition of extract had no negative effect on the number of yeasts in sourdough fermentation. The study has improved the usage of cephalaria by using water and ethanol extracts in dough.
Keywords: Antioxidant activity; Cephalaria syriaca; cytotoxicity; dough properties; SYRIACA ADDITION; RHEOLOGICAL PROPERTIES; FLOUR; Food Science & Technology